A prospective observational study on persistent postoperative pediatric pain, 4P: The study protocol - Johanna Broman; Niklas Nielsen; Anna K. M. Persson (PLoS ONE, 2025)
Background Access to adequate pain treatment is a fundamental right, yet international data suggest that a considerable number of children experience acute and persistent pain. Little is known about the occurrence of both acute and persistent pain in children. The incidence of persistent postoperative pain in children is an unexplored area but international studies suggest that many children experience long-term pain after surgery, with a major impact on daily life. In 4P, Persistent Postoperative Pediatric Pain, we want to estimate the incidence of acute and persistent postoperative pediatric pain. The European Society for Paediatric Anaesthesiology has developed guidelines for perioperative pain management. We aim to examine how well these guidelines are followed and whether adherence to guidelines influences the pain experienced after surgery. Method 4P is a prospective observational study of children aged 1–17, planned for surgery in southern Sweden 2023–2024. After agreement from all caregivers, data concerning preoperative pain, pre-emptive analgesia, perioperative management and postoperative pain will be collected. Via an electronic management software, pain will be evaluated at home (or in hospital) at 24h, 3, 6 and 12 months after surgery. We will include 1000 patients. Discussion 4P will prospectively follow a large number of children after general pediatric surgeries and evaluate the occurrence of postoperative pain, both acute (APOP) and persistent (PPOP). The study will assess pain treatment regimens and identify risk factors associated with the development of acute and persistent pediatric postoperative pain. Trial registration Prospectively posted at ClinicalTrials.gov, identifier NCT06035042.